Cardiac botryomycosis: an autopsy report. Issue 8 (28th July 2008) - Gupta, K; Das, A; Radotra, B D; Bhalla, A
Abstract : Visceral botryomycosis is rare, and documented sites are lung, brain, kidney, liver and prostate. This report describes a rare autopsy case of disseminated visceral botryomycosis, with bulky, grape-like botryomycotic vegetations in the heart, and similar abscesses in the lungs and bone marrow. This is the first such report in the literature to the best of our knowledge.